Decreasing Radiation Exposure in Pediatric Trauma Related to Cervical Spine Clearance: A Quality Improvement Project. Issue 1 (January 2018) - Waddell, Valerie Ann; Connelly, Susan
Abstract : Study Design: Quality improvement project. Objectives: Reduce the amount of radiation exposure in the pediatric trauma population 5 years of age and older in relation to cervical spine clearance. Background: The evaluation of pediatric cervical spine injuries must be accurate and timely to avoid missed injuries. The difficult clinical examination in pediatric trauma patients necessitates the use of radiologic examinations to avoid missing catastrophic injuries. However, exposure to radiation at an early age increases the pediatric patients' risk of developing cancer (R. A.Kleinerman, 2006 ). Methods: A retrospective chart review was conducted to assess radiation exposure in pediatric patients requiring evaluation for cervical spine clearance. Surgical staff and emergency department physicians received education on the risks related to pediatric radiation exposure and information related to the institution's diagnostic trends for cervical spine clearance. An algorithm was then developed to assist with determining the necessary imaging study for cervical spine clearance. Radiation exposure was monitored following initial education and use of the algorithm to determine its effect on radiation exposure. Results: The retrospective chart review identified cervical spine computed tomography (CT) in 34%, with an average radiation exposure of 3.5 mSv. Following education and introduction of an algorithm, 18% of patients underwent CT for cervical spine clearance with an average radiation exposure of 3.2 mSv, representing a 47% decrease in the use of CT. Conclusion: Staff education and the use of an algorithm show promise in the reduction of radiation exposure and provide safe, effective clearance of the cervical spine in pediatric trauma. Abstract : Supplemental Digital Content is Available in the Text.